Theoretical and Applied Issues of Implementing the Transitional Justice Model in Ukraine - Filatov, Viktor; Boiko, Oleksandr; Нerasymchuk, Sergey; Yefimova, Inna; Pylypenko, Anzhelika (Jurnal Cita Hukum, 2026)
The article provides a comprehensive analysis of the theoretical and applied issues concerning the transitional justice model implementation in Ukraine. The authors have systematized and examined in detail the following issues: a lack of complete understanding regarding the philosophical and analytical nature of the transitional justice model; the absence of retrospective links in the formation and development of the transitional justice model within modern international law; imperfections in theoretical provisions regarding the structural integrity of the transitional justice model; functional limitations of the transitional justice model; a misunderstanding of the grounds for applying the directions and principles of transitional justice; fragmentary understanding of specific transitional justice categories; and the reduction of the transitional justice model solely to the sphere of judicial proceedings. The study summarizes the following factors contributing to these theoretical and applied problems: 1) insufficient level of approbation and scientific substantiation of the transitional justice model at the national level; 2) a lack of institutional links between the scientific community and authorities regarding the shaping of transitional period policies; 3) a failure to comprehend the integrity of the transitional justice model and the unity of its components; 4) the individuality of transitional justice contexts in specific states; 5) insufficient exploration of the philosophical sources of the transitional justice model; 6) imperfections in the cognitive algorithms used to study the transitional justice model